Clinical and sociodemographic comparison of people at high‐risk for psychosis and with first‐episode psychosis. (20th August 2012) - Zimbrón, J.; Ruiz de Azúa, S.; Khandaker, G. M.; Gandamaneni, P. K.; Crane, C. M.; González‐Pinto, A.; Stochl, J.; Jones, P. B.; Pérez, J.
<x xml:space="preserve">Abstract</x> Zimbrón J, Ruiz de Azúa S, Khandaker GM, Gandamaneni PK, Crane CM, González‐Pinto A, Stochl J, Jones PB, Pérez J. Clinical and sociodemographic comparison of people at high‐risk for psychosis and with first‐episode psychosis. Objective: To compare clinical and sociodemographic characteristics previously associated with psychosis, between individuals at high‐risk for psychosis (HR) and patients experiencing a first episode psychosis (FEP), to achieve a better understanding of factors associated with psychosis. Method: Cross‐sectional comparison of 30 individuals at HR with 30 age‐gender matched FEP, presenting to an early intervention service for psychosis. Participants were followed‐up for 2 years to establish the proportion of HR who made the transition into FEP. Results: Both groups showed similar socio‐clinical characteristics, including immigration status, employment history, marital status, family history of psychotic illness, self‐harm and alcohol and drug use. The HR group had a lower level of education, higher burden of trauma, earlier onset of psychiatric symptoms and a longer delay in accessing specialised services. A younger onset of symptoms was associated with a longer delay in accessing services in both groups. After a 2 year follow‐up, only three (10%) of the HR group made a transition into FEP. Conclusion: The similarities observed between individuals at HR and those with FEP suggest that known variables associated with psychosis may be equally prevalent in people at HR who do not develop a psychotic disorder.